Impact of diagnosis-intervention packet payment on the consistency of hospitalization expenses across different medical insurance schemes in China - Jin Zi-Qian; Li Yi-Le; Tao Ying-Ying; Shen Ke-Yi; Lin Xin-Hao; Pei Tong; Li Cheng-Cheng; Wu Dan; Meng Xue-Hui (Frontiers in Public Health)
BackgroundThe Diagnosis-Intervention Packet Payment (DIP) system is regarded as a localized cost-control strategy in China. It aims to improve healthcare efficiency, curb the growth of medical expenses, and optimize the allocation of medical resources among diverse groups.ObjectiveThis study aims to assess the impact of DIP payment reforms on differential changes in patients’ hospitalization expense and to explore the degree of concentration of hospitalization expense for patients with different insurance schemes undergoing treatment for typical diseases, with a view to providing policy recommendations for improving the medical insurance system.MethodsData were collected from patients with cerebral infarction (CI) and coronary atherosclerotic heart disease (CAD) treated at primary, secondary, and tertiary hospitals in S City of China, from 2020 to 2023. Patients were classified into the Urban Employees’ Basic Medical Insurance (UEBMI) group and the Urban and Rural Residents’ Medical Insurance (URRMI) group based on two health insurance schemes. Propensity Score Matching (PSM) was employed to ensure a balanced sample. The changes and trends in hospitalization expenses across different groups were analyzed using the interquartile Range (IQR), standard deviation (SD), and concentration index.ResultsPost-DIP reform, hospitalization expenses for patients with different diseases at various levels of hospitals have decreased annually. Regarding expenses variation, the standard deviation (SD) of hospitalization expenses for both UEBMI and URRMI exhibited a downward trend, with a decrease in the double-difference value each year. From the perspective of expenses concentration, all concentration indices were less than 0 (statistically significant, p < 0.01), indicating a higher concentration in hospitalization expenses for UEBMI.ConclusionThe DIP reform can effectively increase the concentration of hospitalization expenses, reduce the variability of changes in hospitalization expenses for both UEBMI and URRMI, and drive medical practices toward standardization and consistency. However, the degree of this expense reduction varies among the hospitals at all levels.